SIMULASI NUMERIK PADA ALIRAN AIR TANAH MENGGUNAKAN COLLOCATION FINITE ELEMENT METHOD - SALAMAH, UMMU; ADITSANIA, ANNISA; GUNAWAN, P. H. (E-Jurnal Matematika, 2018)
This research presents a numerical simulation on groundwater flow using collocation finite element method (CFEM). Groundwater flow is known as the flow of water beneath the soil. Generally, groundwater flow is generated due to high hydraulic differences. The CFEM is an approximation solution of the differential equation by assuming the selected analytical function to fulfill the differential equation and setting the residual value turn out zero. Here, this research will discuss the case of groundwater flow on steady state and unsteady state. The results of numerical method CFEM is shown second order in terms of convergence by error. The numerical error in case of constant water flow is obtain 3.62E ? 23 using the grid size 6.1797e ? 07. Moreover, the flow of groundwater is simulated in various of hydraulic conductivity constants.